PENERAPAN PENDEKATAN KONTEKSTUAL ELEMEN INKUIRI DALAM MENULIS LAPORAN OLEH SISWA KELAS VIII SMP SWASTA MARISI MEDAN HELVETIA TAHUN PEMBELAJARAN 2012/2013 - MERRYDONNA CHRISTINA SIMANGUNSONG (Kode : Jurnal Bahasa, 2014)
The application of approach contextual element inquiri in study write reportby student class of VIII SMP private sector of Marisi Medan Helvetia yearstudy 2012/2013. This study aimed to describe the difference of study resultwrite report applying of approach contextual element inquiri and withoutapplying approach contextual element inquiri. Population in this research isall class student of VIII SMP private sector of Marisi Medan Helvetia yearstudy 2012/2013. This research sampel is 30 people from 110 existingpopulation. This research use experiment method of pre-test design groupone post test that is experiment which do not use comparator group. Fromdata processing obtained by result of pre test with mean = 68.86, standard ofdeviasi = 10.33, standard of error = 1.92 and including at category very goodcounted 1 student or 3.33%, good category counted 12 student or 40%,category enough counted 15 student or 50%, and category less counted 2student or 6.66%. Result of post test with mean = 81.11, standard of deviasi10.78%, and standard of error = 2.00. Including at category very goodcounted 5 student or 16.66%, good category counted 23 student or 76.66%,and category enough counted 2 student or 6.66%. From data test result ofand pre-test of post-test got result normal distribution. Of homogeneity testgot that this research sampel come from homogeneous population. After testof normalitas, got by t0 equal to 4.38. Then, t0 consulted with tables of t levelof signifikasi 5% with df=N-1=30-1=29, obtained by level of signifikasi 5%= 2.04. Because obtained t0 bigger than t that is 8.57 > 2.04. so, nulhypothesis (Ho) refused and hypothesis (Ha) accepted. Finally, can beconcluded that there are difference which signifikasi between result of studywrite report applying of approach contextual element inquiri with result ofstudy write report without applying of approach contextual element inquiriby class student of VIII SMP private sector of Marisi Medan Helvetia yearstudy 2012/2013.Keywords: approach contextual, inquiri, writing report.